COVID-19 pandemic: Some observations and a few recommendations - Indira Sharma (Indian Journal of Social Psychiatry, 2020)
The COVID-19 pandemic has emerged as a major challenge for India. There has been a widespread response from different sectors. This article seeks to make pertinent observations on the responses to the pandemic in light of implications for the mental health of the community and give concrete suggestions regarding the same. The main observations include: a “global COVID mass hysteria” is fast spreading, an unbalanced presentation of the pandemic highlighting the negative more than the positive aspects; COVID stress is accounted for by other factors as well; cultural aspect of COVID, the nothing to do syndrome; limitations of webinars/online classes; need for simple coping strategies; causes of domestic violence during COVID lockdown; right to privacy of being COVID positive is not absolute, has to be balanced; emergence of morbidities during lockdown, new and old, physical and mental; attention to COVID-19 is resulting in less attention to non-COVID cases; and the major problems of persons with mental illness, especially those with severe mental illness and substance use disorders. The recommendations are balanced education on COVID-19; a pragmatic model of coping, which includes a healthy lifestyle, positive cognitions, and instrumental help to the needy; periodic review of strategies; early detection and treatment of mental illness; re-calibration of health services; continuous supply of medication to persons with mental illness on maintenance therapy; and simple home-based de-addiction.